ASPEK HUKUM KESELAMATAN PENERBANGAN - Agus Pramono (Masalah-Masalah Hukum, 2013)
Chicago Convention, 1944 is an instrument of international law which is produced by the International Civil Aviation Organization (/CAO), regulate international civil aviation including aviation safety material that binds to all /CAO member States. Aircraft is a high-tech product in order to set aviation safety requirements and regulations are very strict non-negotiable slightest. The regulations are very strict in the aviation world devoted to creating a safe flight. Realization of aviation safety depends on a variety of factors related to both quality and disciplined crew, passenger awareness of the importance of aviation safety (body and protective facilities) and natural factors.